Internet of Things and Personalized Healthcare Systems - Krishna, P. Venkata; Gurumoorthy, Sasikumar; Obaidat, Mohammad S. (SpringerBriefs in Forensic and Medical Bioinformatics, 2019)
IX, 132 p. 61 illus., 44 illus. in color.